(untitled) (American Journal of Pedagogical and Educational Research, 2026)
This article examines enantiosemy as a phenomenon in which a single lexical unit develops opposing meanings across different contexts. Rather than treating enantiosemy as an isolated irregularity, the study approaches it as part of broader processes of meaning construction shaped by cognitive, structural, and pragmatic factors. The analysis is based on two comparable corpora of English and Uzbek, each consisting of approximately one million tokens and covering both formal and informal discourse. The findings show that enantiosemy is not random, but emerges through systematic mechanisms such as metaphorical extension, contextual reinterpretation, and shifts in pragmatic focus. While both languages rely on similar cognitive processes, their structural organization leads to different patterns of realization. English data demonstrate a predominance of lexical enantiosemy, whereas Uzbek exhibits a greater reliance on phraseological and morphologically conditioned forms. The study argues that semantic polarity should be understood as a context-sensitive and dynamically constructed phenomenon rather than a fixed lexical property. These results contribute to ongoing discussions in cognitive semantics and offer practical implications for translation, where meaning interpretation depends heavily on discourse context.